**CONCEPT: **The question tests on the basics of exponents and fractions

**SOLUTION: **

3/N = 3/3^P

P=M+1

=>3/N = 3/ 3^(M+1) (Substituting P=M+1)

=3^[1-(M+1)] = 3^(-M ) (Powers are subtracted when bases are same and divided)

=1/3^M

**(OPTION A)**

Modified on: Tue, 12 Oct, 2021 at 12:29 PM

**CONCEPT: **The question tests on the basics of exponents and fractions

**SOLUTION: **

3/N = 3/3^P

P=M+1

=>3/N = 3/ 3^(M+1) (Substituting P=M+1)

=3^[1-(M+1)] = 3^(-M ) (Powers are subtracted when bases are same and divided)

=1/3^M

Did you find it helpful? Yes No

Send feedbackSorry we couldn't be helpful. Help us improve this article with your feedback.

Help Desk Software
by Freshdesk